The melREDCA Operon Encodes a Utilization System for the Raffinose Family of Oligosaccharides in Bacillus subtilis - Morabbi Heravi, Kambiz (J Bacteriol, 2019)
Bacillus subtilis is a heterotrophic soil bacterium that hydrolyzes different polysaccharides mainly found in the decomposed plants. These carbohydrates are mainly cellulose, hemicellulose, and the raffinose family of oligosaccharides (RFOs). RFOs are soluble α-galactosides, such as raffinose, stachyose, and verbascose, that rank second only after sucrose in abundance. Genome sequencing and transcriptome analysis of B. subtilis indicated the presence of a putative α-galactosidase-encoding gene (melA) located in the msmRE-amyDC-melA operon. Characterization of the MelA protein showed that it is a strictly Mn(2+)- and NAD(+)-dependent α-galactosidase able to hydrolyze melibiose, raffinose, and stachyose. Transcription of the msmER-amyDC-melA operon is under control of a σ(A)-type promoter located upstream of msmR (P(msmR)), which is negatively regulated by MsmR. The activity of P(msmR) was induced in the presence of melibiose and raffinose. MsmR is a transcriptional repressor that binds to two binding sites at P(msmR) located upstream of the −35 box and downstream of the transcriptional start site. MsmEX-AmyCD forms an ATP-binding cassette (ABC) transporter that probably transports melibiose into the cell. Since msmRE-amyDC-melA is a melibiose utilization system, we renamed the operon melREDCA. IMPORTANCE Bacillus subtilis utilizes different polysaccharides produced by plants. These carbohydrates are primarily degraded by extracellular hydrolases, and the resulting oligo-, di-, and monosaccharides are transported into the cytosol via phosphoenolpyruvate-dependent phosphotransferase systems (PTS), major facilitator superfamily, and ATP-binding cassette (ABC) transporters. In this study, a new carbohydrate utilization system of B. subtilis responsible for the utilization of α-galactosides of the raffinose family of oligosaccharides (RFOs) was investigated. RFOs are synthesized from sucrose in plants and are mainly found in the storage organs of plant leaves. Our results revealed the modus operandi of a new carbohydrate utilization system in B. subtilis.